IMPLEMENTASI METODE AL MIYAH UNTUK MOTIVASI BELAJAR DAN PEMAHAMAN KAIDAH NAHWU SISWA: Studi di Madrasah Diniyah Progresif Bumi Shalawat Sidoarjo - Sattar, Abdulloh; Rofiq , Ainur (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This study aims to analyze the form of learning Al Miyah method in improving learning motivation and understanding of students' nahwu rules. To analyze the implementation of the Al Miyah method in increasing learning motivation and understanding of student nahwu rules. To analyze the obstacles in the implementation of the Al Miyah method in increasing learning motivation and understanding of student nahwu rules. Qualitative methods will be used in this research. The type of research used is descriptive qualitative, which aims to describe and analyze events, activities and events either individually or in groups. The results of the research form the Al Miyah method in the form of lectures to convey material, songs to remember material and sorogan to determine the ability of students to understand the material. While the implementation is in the form of opening, core and closing activities. The obstacles experienced are the lack of coordination between teachers, student backgrounds, not according to interests and fatigue.